Entrepreneurial spillovers over space and time - Frank M. Fossen; Thorsten Martin (Deutsches Institut für Wirtschaftsforschung (DIW), 2016)
Entrepreneurship is a local and dynamic phenomenon. We jointly investigate spatial spillovers and time persistence of regional new business formation. Using panel data from all 402 German counties for 1996-2011, we estimate dynamic spatial panel models of business creation in the high-tech and manufacturing industries. We consider regions of different sizes and systematically search for the most suitable spatial weighting matrices. We find substantial spatial spillovers as well as time persistence of start-up activity, especially in the high-tech industry. This indicates that entrepreneurship is deeply rooted in regions and underlines the importance of local entrepreneurship culture for new business formation.
Keywords: L26; C23; R12; O30; 330; entrepreneurship; new business formation; spatial spillovers; path dependency; persistence; spatial panel